When education policy and housing policy interact: Can they correct for the externalities? - Yifan Gong; Charles Ka Yui Leung (Osaka University, Institute of Social and Economic Research (ISER), 2020)
We develop a simple spatial equilibrium model with the peer group effect and local public finance to analyze the implications of housing policies such as public housing and housing voucher programs, and education policies such as school finance consolidation. The calibrated model can match several stylized facts of the labor market and the housing market in the United States. Our counterfactual policy analyses suggest that public housing and housing voucher programs have similar welfare implications on the household level. However, within a household, the public housing program tends to benefit the children more than the parents, while the housing voucher program delivers the opposite result. Combining the school finance consolidation policy with the public housing program could improve the well-being of children from poor households without hurting other households' welfare. Some policies' short-run welfare implications can deviate significantly from their long-run counterparts when all choices are optimized.
Keywords: H00; I20; R00; 330; school finance consolidation; public housing; housing voucher; endogenous sorting mechanism; short-run rigidity versus long-run flexibility